At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

What is the solution to the linear equation?

[tex]\[ 4b + 6 = 2 - b + 4 \][/tex]

A. [tex]\( b = -2 \)[/tex]
B. [tex]\( b = 0 \)[/tex]
C. [tex]\( b = 4 \)[/tex]
D. [tex]\( b = 6 \)[/tex]


Sagot :

To solve the linear equation [tex]\(4b + 6 = 2 - b + 4\)[/tex], follow these steps:

1. Start with the given equation:
[tex]\[ 4b + 6 = 2 - b + 4 \][/tex]

2. Combine like terms on the right side:
[tex]\[ 4b + 6 = 6 - b \][/tex]

3. Add [tex]\(b\)[/tex] to both sides to eliminate the variable on the right:
[tex]\[ 4b + b + 6 = 6 \][/tex]

4. Simplify the equation:
[tex]\[ 5b + 6 = 6 \][/tex]

5. Subtract 6 from both sides to isolate the term with the variable:
[tex]\[ 5b = 0 \][/tex]

6. Divide both sides by 5 to solve for [tex]\(b\)[/tex]:
[tex]\[ b = 0 \][/tex]

Therefore, the solution to the equation is [tex]\(b = 0\)[/tex]. The correct answer is:
[tex]\[ \boxed{0} \][/tex]

Answer:

hello

Step-by-step explanation:

4b+6 = 2-b+4

4b+b=6-6

5b=0

b=0